READING DIFFICULTIES ON EFL LEARNERS: (A CASE STUDY ON THE FIRST SEMESTER OF MANAGEMENT PROGRAM AT ISLAMIC UNIVERSITY OF INDRAGIRI TEMBILAHAN) - Maizarah Maizarah (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The problem in this study was the students’ reading difficulties on EFL Learners. This study only used one variable. The research method used in this study was a descriptive research. The purpose of this study was to know the students’ reading difficulties in English as a foreign language at the first semester of Management Program at Islamic University of Indragiri Tembilahan. The total of the population used in this study were 163 students, the technique was used to take the sample is random sampling, the sample of this study was 25% from the population were 41 students. In collecting the data, the researcher used a close-ended questionnaire and an open-ended questionnaire. After the data has been collected, the result of close-ended questionnaire shows that the most problem is faced by the students related to oral reading difficulties is lacking fluency, as many as 31 students (75,6%) say yes. While, the most problem is faced by the students related to reading comprehension difficulties is inability to understand what has been read due to limited knowledge of vocabulary, as many as 28 students (68,3%) say yes. In addition, the result of open-ended questionnaire are: 1) Some of English words are difficult to pronounce and some of English words are not difficult to pronounce, 2) English words can be difficult to pronounce because of the different writing and the way to pronounce it. 3) The difficulty to pronounce the English words was caused by the English word did not use in their daily activity. 4) English words are difficulties to read with appropriate speed, it is caused by the lack practice of reading sentences in English, 5) The difficulties to understand the word or English sentence because the lack of vocabularies. 6) The biggest reading difficulty in English for most of the studetns were difficult to pronounce the english words and difficult to understand the meaning of English words/sentences, 7) the way to overcome the difficulties in their reading were increase the reading practice and memorize the vocabularies.